Vitality and Dynamism Interstitial Dialogues of Language, Politics, and Religion in Morocco's Literary Tradition - Bratt, Kirstin; Elbousty, Youness; Stewart, Devin (2014)
Post-colonial theory recognizes that European and American scholars have traditionally defined the themes that are of interest in literary criticism; in Moroccan studies, these themes have tended toward questions of migration, identity, secularism, and religious fanaticism typically questions regarding Morocco in its relationships with colonizing nations. This book intends to re-define the themes of interest in Moroccan studies, looking toward more local themes and movements and relationships of sub-cultures and languages within Morocco. Questions in this volume regard concepts of the self, conflicting discourses, intersections of self-identity and community, and Moroccan reclamation of identity in the post-colonial sphere.